Optimizing Regression Testing Efficiency Through Advanced Test Case Prioritization Techniques Using Execution Trace Diversity - Pavan Kalyan, Appari; Pratap Singh, Harsh; Kavitha Rani, B. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Abstract Spectrum-based fault localization (SBFL), which utilizes spectrum information of test cases to calculate the suspiciousness of each statement in a program, can reduce developers’ effort. However, applying redundant test cases from a test suite to fault localization incurs a heavy burden, especially in a restricted resource environment, and it is expensive and infeasible to inspect the results of each test input. Prioritizing/selecting appropriate test cases is important to enable the practical application of the SBFL technique. In addition, we must ensure that applying the selected tests to SBFL can achieve approximately the effectiveness of fault localization with whole tests. This paper presents a test case prioritization/selection strategy, namely the Diversity-Aware Test Optimization (DATO). The DATO strategy prioritizes/selects test cases using information on the diversity of the execution trace of each test case. We implemented and applied the DATO strategy to 233 faulty versions of the Siemens and UNIX programs from the Software-artifact Infrastructure Repository.